4 - La problématique de l'eau en milieu rural ivoirien : aspects méthodologiques et pédagogiques * - DANIEL, Kadja M (Africa Development, 1981)
* Cet article a déjà fait l'objet d'une communication au Ve Congrès Mondial de Sociologie Rurale tenue à Mexico en août 1980 sous le titre, la qualité de la vie et la problématique de l'eau en miieu rural ivoirien The Ivory Coast is undergoing difficulties in the supply of water to the rural areas although it is situated in a wet intertropical zone. These difficulties which are both qualitative and quantitative have been studied for some years now by the administrative authorities together with the rural population on the one hand and by the administrative authorities and some private or semi-private international organisations on the other hand. But the actions of the state towards the solution of the problem of water in But the actions of the state towards the solution of the problem of water in rural areas have not always been clear and coherent even if they had economic, technological, sanitary pedagogical and even political implications. The author's view on the problem can be summarized in the following three points: The solution of the problem of water-supply in the daily life of the rural populations of the Ivory Coast must be analysed as part of a wider problematic of the improvement of the quality of life of rural populations. Therefore, the environment of the rural populations is a qualitative datum which cannot be conceived in terms of isolated and isolable elements. The methodology to be used in that action must necessarily take into account the existing rural communal structures without which genuine integrated rural development cannot be defined. This project should be understood as a starting point for the parti- cipation of rural populations in development by posing the pro- blem of the increase of their autonomy. Kadja M. DANIEL, Chargé de Recherches, Institutd'Ethno-Sociologie, Université Nationale de Côte d'Ivoire.